Implementasi Kebijakan Standar Sarana dan Prasarana di Sekolah Dasar - Liza Murniviyanti; Zulela MS; Edwita Edwita (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
Facilities and infrastructure in elementary schools that are in accordance with the standards of Law Number 20 of 2003 concerning the National Education System, Article 35 will affect the quality of schools. For this reason, the purpose of this study was to describe the implementation of standard policies for facilities and infrastructure in elementary schools including study rooms, places of worship, sports venues, libraries, laboratories, workshops, playgrounds, and other rooms that support the learning process. This research method used a qualitative approach with program analysis methods. This research was conducted at three schools, namely SD Negeri 4, SD Negeri 10, and SD Negeri 15, Sembawa District, Banyuasin Regency. This research method uses a qualitative approach with program analysis methods. Data collection techniques using observation, interviews, and documentation. The researcher conducted direct interviews with the principal of SD Negeri 4 Sembawa, the head of SD Negeri 10 Sembawa, and the head of SD Negeri 15 Sembawa, Banyuasin Regency using triangulation techniques. The results showed that the existing facilities and infrastructure in the school, namely study rooms, prayer rooms, libraries, sports venues, and meeting halls were managed directly by the principal and assisted by teachers and staff at the school. Utilization of facilities and infrastructure has been carried out based on their respective functions. The constraints on facilities and infrastructure are the lack of buildings, school fences, sports venues, and prayer rooms. The impact of the lack of facilities and infrastructure makes students less able to get incomplete facilities in learning, especially there is still a lack of study space and one of the schools still does not have a prayer room.